Coding the future: digital technologists and the constitution of the next system - Deepak, Dhruv; Manski, Ben (Frontiers in Sociology, 2025)
Digital technologists are coding the world of our immediate future. Digital commoners are a subset of digital technologists who aim to expand the spheres of life held in common, strengthen mutual aid, and create the conditions for shared participation in power. Relying on an understanding of technologists as activists, of technology as a movement, and of digital code as constitutional design, we analyze the digital commoners and their movement. Relying on a theory of the constitutive powers of digital technology in the areas of design, affordance, and sovereignty, we examine platform cooperatives, peer production systems, data sovereignty initiatives, and digital governance platforms, and analyze how these initiatives align with broader movements for system change. We argue that digital commoners are producing the elements of a digital commonwealth, a new form of democratic economic polity. Finally, we call on scholars and academic institutions to intervene and support digital commoning efforts, amplifying technologists’ capacity to code the future toward shared goals.